Evaluation of swabbing methods for estimating the prevalence of bacterial carriage in the upper respiratory tract: a cross sectional study. Issue 10 (30th October 2014) - Coughtrie, A L; Whittaker, R N; Begum, N; Anderson, R; Tuck, A; Faust, S N; Jefferies, J M; Yuen, H M; Roderick, P J; Mullee, M A; Moore, M V; Clarke, S C
Abstract : Objectives: Bacterial carriage in the upper respiratory tract is usually asymptomatic but can lead to respiratory tract infection (RTI), meningitis and septicaemia. We aimed to provide a baseline measure of Streptococcus pneumoniae, Moraxella catarrhalis, Pseudomonas aeruginosa, Staphylococcus aureus, Haemophilus influenzae and Neisseria meningitidis carriage within the community. Self-swabbing and healthcare professional (HCP) swabbing were compared. Design: Cross-sectional study. Setting: Individuals registered at 20 general practitioner practices within the Wessex Primary Care Research Network South West, UK. Participants: 10 448 individuals were invited to participate; 5394 within a self-swabbing group and 5054 within a HCP swabbing group. Self-swabbing invitees included 2405 individuals aged 0–4 years and 3349 individuals aged ≥5 years. HCP swabbing invitees included 1908 individuals aged 0–4 years and 3146 individuals aged ≥5 years. Results: 1574 (15.1%) individuals participated, 1260 (23.4%, 95% CI 22.3% to 24.5%) undertaking self-swabbing and 314 (6.2%, 95% CI 5.5% to 6.9%) undertaking HCP-led swabbing. Participation was lower in young children and more deprived practice locations. Swab positivity rates were 34.8% (95% CI 32.2% to 37.4%) for self-taken nose swabs (NS), 19% (95% CI 16.8% to 21.2%) for self-taken whole mouth swabs (WMS), 25.2% (95% CI 20.4% to 30%) for nasopharyngeal swabs (NPS) and 33.4% (95% CI 28.2% to 38.6%) for HCP-taken WMS. Carriage rates of S. aureus were highest in NS (21.3%). S. pneumoniae carriage was highest in NS (11%) and NPS (7.4%). M. catarrhalis carriage was highest in HCP-taken WMS (28.8%). H. influenzae and P. aeruginosa carriage were similar between swab types. N. meningitidis was not detected in any swab. Age and recent RTI affected carriage of S. pneumoniae and H. influenzae . Participant costs were lower for self-swabbing (£41.21) versus HCP swabbing (£69.66). Conclusions: Higher participation and lower costs of self-swabbing as well as sensitivity of self-swabbing favour this method for use in large population-based respiratory carriage studies.